2016
DOI: 10.2147/ott.s123986
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-induced α-catenin downregulation enhances the motility of human colorectal cancer cells in an NF-κB signaling-dependent manner

Abstract: α-Catenin is an important molecule involved in the maintenance of cell–cell adhesion and a prognostic marker in cancer since its expression is essential for preventing cancer metastasis. However, the mechanism that leads to the downregulation of α-catenin in cancer progression remains unclear. The present study revealed that lipopolysaccharide (LPS)-induced NF-κB signaling activation suppressed α-catenin expression and motility in SW620 colorectal cancer (CRC) cells, using real-time polymerase chain reaction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 31 publications
3
9
0
1
Order By: Relevance
“…Despite certain unexpected results, our in vivo study has for the first‐time provided the evidence that systemic administration of LPS could activate NF‐κB in PCa cells (Figures A and B) and enhance PCa cells metastasis in a cell line dependent manner (Figure A). We believe that, this effect could be through both direct and indirect methods of LPS‐mediated NF‐κB activation in PCa cells . No metastasis was observed in our DU145 orthotopic tumor model that confirms previously reported less metastatic nature of these cells .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Despite certain unexpected results, our in vivo study has for the first‐time provided the evidence that systemic administration of LPS could activate NF‐κB in PCa cells (Figures A and B) and enhance PCa cells metastasis in a cell line dependent manner (Figure A). We believe that, this effect could be through both direct and indirect methods of LPS‐mediated NF‐κB activation in PCa cells . No metastasis was observed in our DU145 orthotopic tumor model that confirms previously reported less metastatic nature of these cells .…”
Section: Discussionsupporting
confidence: 90%
“…However, migration assay carried out with LPS‐induced secretory factors (10% plasma) as a chemo‐attractant (lower chamber) indicates that the remarkable increase in the migration of cells might be due to the strong chemo‐attractant properties of LPS‐induced factors (Figure C). The aforementioned, in vitro experiments also supported various other studies that show pro‐migratory properties of LPS on cancer cells . However, in the subsequent experiments, our in vivo data reminded us the commonly known fact that in vitro results might not be always recapitulated in vivo.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The combination of ibuprofen plus LPS was tested in colorectal cancer patients and showed encouraging results. But recently it has been shown that LPS enhance the motility in CRC cells by mediating NF‐κB signaling and α‐catenin suppression (Cheng et al, ).…”
Section: Introductionmentioning
confidence: 99%